Development of a novel optogenetic indicator based on cellular deformations for mapping optogenetic activities. Issue 45 (2nd October 2018) - Li, Gongxin; Yang, Jia; Wang, Yuechao; Wang, Wenxue; Liu, Lianqing
Abstract : We propose a novel optogenetic indicator based on cellular deformation to characterize the activities of optogenetically engineered cells. Abstract : Optogenetic techniques have changed the landscape of neuroscience by offering high temporal and spatial mapping of the activities of genetically defined population of cells with optical controlling tools. The mapping of optogenetic activities demands optogenetic indicators whose optical properties change in response to cellular activities, but the existing optogenetic indicators only specifically characterize limited optogenetic activities. Here, we propose a novel optogenetic indicator based on cellular deformation to characterize the activities of optogenetically engineered cells. The cellular activities triggered by light stimulation lead to changes in the cell membrane structure and result in cellular deformation, which is measured by atomic force microscopy. The deformation recordings of the cells expressing channelrhodopsin-2 (ChR2) and the corresponding control experiments together confirm that the deformation is generated generally when the cells are exposed to light, which is also validated indirectly via the change in the Young's modulus of the cells before and after absorption of photons. The activities of cells expressing different subtypes of opsins were also recorded using the optogenetic indicator of cellular deformation. This study provides a novel and general optogenetic indicator based on cellular deformation for monitoring the activities of optogenetically engineered cells. Moreover, this new optogenetic indicator offers ever-better tools for the applications of optogenetic activity mapping and neural and brain imaging.